Evaluasi Perencanaan Saluran Drainase Jalan Sepakat Kecamatan Payung Sekaki Kota Pekanbaru - Soehardi, Fitridawati; Lubis, Fadrizal; Safdivah, Yohanda (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2025)
Sepakat Street, Payung Sekaki District, had puddles on the road surface even though it already has drainage channels on the right and left of the drain with a depth of 0.4 m and a width of 0.6 m. The purpose of this research is to evaluate the planning to improve the condition of the existing drainage channels so that they can drain water. The method used is the Gumbel distribution method to calculate the frequency of rainfall, SNI 03-3424-1994 to calculate rainfall intensity, and the Manning method to calculate flow velocity. Then the results of evaluation calculations on the drainage channel on the road agreed, Payung Sekaki sub-district, Pekanbaru City with dimensions of 0.6 meters wide and 0.4 meters high, obtained that the discharge of the existing channel that can accommodate water on the right is 0.0621 m³/s, and on the left is 0.071 m³/sec, and the total discharge from the discharge and rainfall on the right is 1.20401 m³/sec, and the left is 1.20411 m³/sec. Payung Sekaki, Pekanbaru City, the cause is that the drainage cannot accommodate the existing water discharge so there is a puddle on the road in the Sekaki Payakumbuh sub-district, Pekanbaru City, and after being re-planned according to the existing discharge, the dimensions have been planned for the right and left channels with a width of 0.6 meters and depth of 1.05 meters.